A 3D numerical analysis using phase change material for cooling circular light emitting diode. (March 2023) - Ben Hamida, Mohamed Bechir; Hajlaoui, Khalil; Almeshaal, Mohammed A.
Abstract: This paper's goal is to find the impact of incorporation of Phase Change Material (PCM) in the heat sink for improving the cooling performance of circular Light Edding Diode (LED). A 3D numerical model using Comsol Multiphysics is was created to model the PCM melting process while taking natural convection into account. The ''Paraffin'' is inserted in the central cavity of the heat sink. After validation of this model with previously published works, the effect of power input on the PCM's effectiveness was investigated. The results found that using PCM in the heat sink allowed for a reduction in junction temperature during the melting process for 11.17%, 15.59%, 18.02%, 19.54%, 20.58% and store energy of 110 kJ/kg, 129.25 kJ/kg, 148.78 kJ/kg, 168.06 kJ/kg, 187.3 kJ/kg when the circular LED is powered 1 W, 2 W, 3 W, 4 W and 5 W, respectively. This quantity of energy will be released into the surrounding space to heat it. In addition, the PCM has a notable impact on lowering the temperature but only for a brief period of time. This effect increases as the power input rises.